INFLUENCE OF CHLORAMPHENICOL ON THE EMBRYOS AND LARVAE OF TOAD, BUFO ANDERSONII (BOULENGER) - SAXENA, SAROJ (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
Embryos and larvae of toad, Bufo andersonii were reared in 0.05%, 0.1%, 0.2%, 0.3% & 0.4% solutions of chloramphenicol from early blastula stage onwards at room temperature for 10 days. Chloramphenicol did not affect hatching but caused severe mortality, dehydration, skin depigmentation and growth inhibition of the larvae. This effect was correlated with the amount of chloramphenicol present in the rearing medium. Frequency of mortality was low in larvae treated with 0.05% and 0.1% chloramphenicol but was much greater in those treated with 0.2%, 0.3% and 0.4% chloramphenicol.